2023
DOI: 10.3390/en16093916
|View full text |Cite
|
Sign up to set email alerts
|

Research on Electromagnetic Vibration Characteristics of a Permanent Magnet Synchronous Motor Based on Multi-Physical Field Coupling

Abstract: Background and Purpose: The stator vibration characteristics are comprehensively mastered by considering the influence of winding and the housing structure on the stator modes. This effect is neglected in the research field of electromagnetic vibration of permanent magnet synchronous motors (PMSMs). Methods: The radial air-gap flux density equations and PMSM’s electromagnetic force density are derived, and then the harmonic characteristics of electromagnetic force density are studied. An equivalent finite elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The structural characteristics of the motor have a large impact on its vibration noise. Resonance occurs when the frequency of electromagnetic force closely matches the natural frequency, which in turn worsens the NVH performance of the motor [31]. In this paper, finite element analysis is performed in JMAG to obtain the modal parameters of the prototype.…”
Section: Modal Analysismentioning
confidence: 99%
“…The structural characteristics of the motor have a large impact on its vibration noise. Resonance occurs when the frequency of electromagnetic force closely matches the natural frequency, which in turn worsens the NVH performance of the motor [31]. In this paper, finite element analysis is performed in JMAG to obtain the modal parameters of the prototype.…”
Section: Modal Analysismentioning
confidence: 99%
“…In this study, the mass of the transmission shaft is unchanged, and the natural frequency and mode of each order under different stiffness are studied by analytical calculation in the simulation model. For an approximately cylindrical driveshaft, the M-order circumferential natural frequency can be expressed as [21]:…”
Section: Modal Analysismentioning
confidence: 99%
“…Moreover, higher-order electromagnetic forces with frequencies close to the motor's natural frequency were found to be susceptible to resonance, intensifying vibration noise. Reference [5] revealed that a mismatch in the spatial order of radial electromagnetic forces and the order of stator modes may lead to resonance-induced vibration noise due to the proximity of the electromagnetic force frequency to the stator's natural frequency. While these studies have elucidated the reasons behind the generation of vibration noise from radial electromagnetic forces, specific strategies for mitigating vibration noise have not been explicitly proposed.…”
Section: Introductionmentioning
confidence: 99%